European Young Professionals' Forum. Conference documentation. 12 - 13/10/2010, Mannheim, Germany. Challenges of European Spatial Development: Young Professionals' and Researchers' Perspectives. - (:unkn) unknown (My University, 2011)
Nach einem themenübergreifenden Beitrag von Simin Davoudi "European spatial development: Why Territorial Cohesion matters?" werden drei Felder bearbeitet. Die räumliche Kohäsion mit Beiträgen über "Decoding cultural phenomena of Territorial Cohesion" und "Big regions - big benefit? Strategies of Territorial Cohesion in fuzzy regions" sowie "Private enterprises and Territorial Cohesion: How does it work?" Zweiter Schwerpunkt ist der demographische Wandel mit dem Beitrag über Schrumpfungsprozesse in Sachsen-Anhalt und Überalterung im ländlichen Raum in Österreich sowie Überlegungen zur Bedeutung von Informations- und Kommunikationsmedien in der Regionalentwicklung. Mit dem Thema Klimawandel befassen sich ein Vergleich von Bratislava und Leipzig hinsichtlich der Integration von Mitigationsmaßnahmen in die räumliche Planung sowie eine Übersicht über die unterschiedlichen Klimawandelstrategien in ländlichen Räumen Europas.

The aging and decreasing of the population will lead to considerable problems on the residential property market in sparsely populated, rural regions not close to large cities. Property values will fall to the extent that it will be impossible to sell, and buildings will stand vacant in villages and small towns. The following questions form the focus of attention for a subsection drawn from the regional working group of Hesse, Rhineland-Palatinate and Saarland: What are the vacancy rates? How does this affect the appearance of the villages? In what ways can the municipalities, the state, and property institutions provide planning, political and financial help in this area? The subsection aims to provide a pilot study that demonstrates options and methods for dealing with residential vacancies in rural areas. Three examples are used to illustrate methods of compiling and forecasting vacancy rates. This forms the basis for assessing the suitability of informal, financial and legal instruments that may increase the value and usability of residential property in rural areas.
Keywords: Raumordnung; Raumplanung; Kohäsion; Ländlicher Raum; Bevölkerungsentwicklung; Siedlungsentwicklung; Schrumpfung; Alterung; Prognose; Zusammenhalt; Klimawandel